1999
DOI: 10.1200/jco.1999.17.9.2639
|View full text |Cite
|
Sign up to set email alerts
|

Multinational Study of the Efficacy and Safety of Humanized Anti-HER2 Monoclonal Antibody in Women Who Have HER2-Overexpressing Metastatic Breast Cancer That Has Progressed After Chemotherapy for Metastatic Disease

Abstract: Recombinant humanized anti-HER2 monoclonal antibody, administered as a single agent, produces durable objective responses and is well tolerated by women with HER2-overexpressing metastatic breast cancer that has progressed after chemotherapy for metastatic disease. Side effects that are commonly observed with chemotherapy, such as alopecia, mucositis, and neutropenia, are rarely seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
1,438
3
30

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,541 publications
(1,506 citation statements)
references
References 22 publications
19
1,438
3
30
Order By: Relevance
“…These results indicate that HercepTest 3 þ patients in oesophageal SCC will be the best candidates for anti-HER-2 immune targeting. It has already been shown in breast cancer trials that there is a greater benefit from Herceptin therapy for 3 þ patients compared to those who were 2 þ (Cobleigh et al, 1999;Slamon et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that HercepTest 3 þ patients in oesophageal SCC will be the best candidates for anti-HER-2 immune targeting. It has already been shown in breast cancer trials that there is a greater benefit from Herceptin therapy for 3 þ patients compared to those who were 2 þ (Cobleigh et al, 1999;Slamon et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Initial trials showed it was well tolerated and produced durable response in patients who had failed first‐ and second‐line chemotherapy 21, 22, 23. Subsequent large, phase III trials showed significant improvements in time to treatment failure and overall mortality in patients with progressive metastatic breast cancer 5.…”
Section: The Benefits Of Her2 Targeted Therapiesmentioning
confidence: 99%
“…Monoclonal antibodies (mAbs) are an important class of biomolecules that are used in the treatment of various diseases such as cancer, multiple sclerosis, rheumatoid arthritis, lupus, and respiratory diseases (Choy et al, 1998; Cobleigh et al, 1999; Haynes et al, 2009; Helliwell and Coles, 2009; Robak and Robak, 2009). During mAb process development, aggregates and fragments have to be removed to adequate levels due to their associated risks with increased immunogenicity and potential effects on drug efficacy (Fan et al, 2012; Rosenberg, 2006).…”
Section: Introductionmentioning
confidence: 99%